"It's Almost as if Stakeholder Engagement is the Annoying 'Have-to-do'…": Can Ethics Review Help Address the "3 Ts" of Tokenism, Toxicity, and Tailoring in Stakeholder Engagement?. (July 2022) - Wilkinson, Abigail; Slack, Catherine; Thabethe, Siyabonga; Salzwedel, Jessica
Ethics guidance recommends that researchers engage stakeholders and that RECs review research for such engagement. The ethics review process may present a unique opportunity to support stakeholder engagement practices for HIV prevention studies. We conducted 28 interviews with experts from 12 countries to explore this issue, and analyzed the data using Thematic Analysis. We found that the value of engagement and review processes was strongly endorsed. However, we identified 3 major thematic complexities, namely: "Tokenism" where processes risk being "tick-box"; "Toxicity", where practices may inadvertently have negative consequences; and "Tailoring", where processes need careful variation in intensity. We make recommendations for how these "Ts" can be addressed during the review process to help contribute to thoughtful review of meaningful stakeholder engagement in research.